Narrating Suffering, Remembering Hope: Metz's Theology as Paradigm for Examining Mental Illness and Disability Theology - Stetler, Emily (Journal of religion, disability & health, 2013)
This article proposes to explore new ways of speaking about disability by drawing from the theology of Johann Baptist Metz. Specifically, it uses Metz's ideas of subjectivity, narrative, memory, and hope and applies them to mental illness, with the intent to enable theologians to respond to mental health issues in a more nuanced way and to encourage Christians to foster a deeper solidarity with those suffering from mental illness. The article then briefly considers how Metz's paradigm may be used to enhance our understanding of other categories of disability.